2001
DOI: 10.1029/1999jc000101
|View full text |Cite
|
Sign up to set email alerts
|

Isopycnal Lagrangian statistics from the North Atlantic Current RAFOS float observations

Abstract: Abstract. One hundred isopycnal floats were tracked on the 27.2 and 27.5 o-0 surfaces in the Newfoundland Basin (NFB) from July 1993 to July 1995 to study the current structure and exchanges of waters between the subtropical and subpolar gyres. The float-mapped mean flow consists of weak flows in the NFB and a strong boundary current (the North Atlantic Current (NAC)), which separates from the boundary at the Northwest Corner, becoming a diffusive zonal drift. The NAC meanders are linked to topography and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 37 publications
12
85
0
Order By: Relevance
“…We note that the integral timescale (about 1.71 days) and the diffusivity K (1.17 × 10 3 m 2 s −1 ) are of the same order of magnitude as those found for ocean drifters (e.g., Poulain and Niiler, 1989;Zhang et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…We note that the integral timescale (about 1.71 days) and the diffusivity K (1.17 × 10 3 m 2 s −1 ) are of the same order of magnitude as those found for ocean drifters (e.g., Poulain and Niiler, 1989;Zhang et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…This is done here by following the classical approach used to study Lagrangian particle trajectories (see for example Zhang et al, 2001). This consists of splitting each trajectory into mean and fluctuating parts by using appropriate averaging scales L and T to compute the Lagrangian mean motion at any given location and time.…”
Section: Decomposition Of the Sea-ice Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is different from other regions such as the surface over the California Current (Swenson and Niiler 1996) and subsurface in the Newfoundland Basin (Zhang et al 2001).…”
Section: A the Pdf Of Residual Velocitymentioning
confidence: 99%
“…However this rule is not universal. In fact, subsequent studies showed that a constant-T rule did not apply elsewhere and suggested that the diffusivity scales with the rms velocity (Krauss and Boning 1987;Brink et al 1991;Zhang et al 2001). Thus, in the future remains to determine what are the dynamical regimes that make the constant-T rule regionally applicable.…”
Section: Discussionmentioning
confidence: 99%